Whole‐building decontamination of Bacillus anthracis Sterne spores by methyl bromide fumigation - Serre, S. (J Appl Microbiol, 2015)
AIMS: To evaluate the field inactivation of Bacillus anthracis Sterne spores with methyl bromide (MB) using commercial fumigation techniques. METHODS AND RESULTS: Eighty‐seven wood and 87 glass coupons each containing ca. 1 × 10(6) B. anthracis Sterne spores, were placed in 22 locations inside a 1444 m(3) conference building. Four additional 12‐coupon sets (six wood, six glass) were removed from the building at 16, 24, 32 and 40 h during fumigation. The building was sealed under two tarpaulins and fumigated with MB at ≥225 g m(−3) mean concentration for 48 h at 28°C and 83% RH. All B. anthracis spores fumigated for more than 16 h were inactivated. A single wood coupon from the 16‐h set yielded ca. 2 × 10(3) CFU. No damage to the building or its contents was observed. CONCLUSIONS: MB fumigation is a rapid, economical and effective whole‐structure decontamination method for B. anthracis spores. SIGNIFICANCE AND IMPACT OF THE STUDY: MB fumigation offers a method of whole‐structure B. anthracis decontamination without removal of materials, damage to sensitive electronics, costly indoor retrofitting.